Can an extracorporeal glenoid aiming device be used to optimize the position of the glenoid component in total shoulder arthroplasty? - Verstraeten, Tom R. G. M. (Int J Shoulder Surg, 2015)
PURPOSE: Successful total shoulder arthroplasty (TSA) requires a correct position of the glenoid component. This study compares the accuracy of the positioning with a new developed glenoid aiming device and virtual three-dimensional computed tomography (3D-CT) scan positioning. MATERIALS AND METHODS: On 39 scapulas from cadavers, a K-wire (KDev) was positioned using the glenoid aiming device. It consists of glenoid components connected to the aiming device, which cover 150° of the inferior glenoid circle, has a fixed version and inclination and is available with several different radii. The aiming device is stabilized at the most medial scapular point. The K-wire is drilled from the center of the glenoid component to this most medial point. All scapulas were also scanned with CT and 3D reconstructed. A virtual K-wire (Kct) was positioned in the center of the glenoid and in the scapular plane. Several parameters were compared. Radius of the chosen glenoid component (rDev) and the virtual radius of the glenoid circle (rCT), spinal scapular length with the device (SSLdev) and virtual (SSLct), version and inclination between KDev and Kct, difference between entry point and exit point (“Matsen”-point). RESULTS: Mean rDev: 14 mm ± 1.7 mm and mean rCT: 13.5 mm ± 1.6 mm. There was no significant difference between SSLdev (110.6 mm ± 7.5 mm) and SSLct (108 mm ± 7.5 mm). The version of KDev and Kct was −2.53° and −2.17° and the inclination 111.29° and 111.66°, respectively. The distance between the “Matsen-point” device and CT was 1.8 mm. CONCLUSION: This glenoid aiming device can position the K-wire on the glenoid with great accuracy and can, therefore, be helpful to position the glenoid component in TSA. The level of evidence: II.